Risk of venous thromboembolism in users of oral contraceptives containing drospirenone or levonorgestrel: nested case-control study based on UK General Practice Research Database - Parkin, Lianne (BMJ Publishing Group Ltd., 2011)
Objective To examine the risk of non-fatal idiopathic venous thromboembolism in current users of a combined oral contraceptive containing drospirenone, relative to current users of preparations containing levonorgestrel. Design Nested case-control study. Setting UK General Practice Research Database. Participants Women aged 15-44 years without major risk factors for venous thromboembolism who started a new episode of use of an oral contraceptive containing 30 µg oestrogen in combination with either drospirenone or levonorgestrel between May 2002 and September 2009. Cases were women with a first diagnosis of venous thromboembolism; up to four controls, matched by age, duration of recorded information, and general practice, were randomly selected for each case. Main outcome measures Odds ratios and 95% confidence intervals estimated with conditional logistic regression; age adjusted incidence rate ratio estimated with Poisson regression. Results 61 cases of idiopathic venous thromboembolism and 215 matched controls were identified. In the case-control analysis, current use of the drospirenone contraceptive was associated with a threefold higher risk of non-fatal idiopathic venous thromboembolism compared with levonorgestrel use; the odds ratio adjusted for body mass index was 3.3 (95% confidence interval 1.4 to 7.6). Subanalyses suggested that referral, diagnostic, first time user, duration of use, and switching biases were unlikely explanations for this finding. The crude incidence rate was 23.0 (95% confidence interval 13.4 to 36.9) per 100 000 woman years in current users of drospirenone and 9.1 (6.6 to 12.2) per 100 000 woman years in current users of levonorgestrel oral contraceptives. The age adjusted incidence rate ratio was 2.7 (1.5 to 4.7). Conclusions These findings contribute to emerging evidence that the combined oral contraceptive containing drospirenone carries a higher risk of venous thromboembolism than do formulations containing levonorgestrel.